Female subjugation and liberation: an ecofeminist study of the selected novels of Shashi Deshpande and Bapsi Sidhwa - Raza, Sobia (2025)
Utilising the lenses of cultural ecofeminism and material ecofeminism, this study attempts to understand women's subjugation by patriarchy. Societal constructs are mostly built around dualism, women and their nature versus men and culture, wherein women and nature are regarded as inferior, and used for subjugation. This thesis also investigates how the institution of marriage, religion, and mythological beliefs are abused to dominate women in the societies of Pakistan and India as depicted by Bapsi Sidhwa in “The Bride” and Shashi Deshpande in “The Dark Holds No Terrors.” Women are forced to give up their identities and fundamental rights. Better health care, education, economic independence, and the right to make decisions for their lives are often denied in these societies. Women, nature, land, and animals are placed in parallel. They are exploited by men like non-living entities. For instance, women are often divorced by men if they cannot produce children. They are equated to barren land in these societies. They are killed for suspected infidelities and traded for settling blood feuds and financial debts. This research primarily focuses on female suppression and their independence. Material ecofeminism helps in understanding the ongoing exploitation of women, nature and other species for material gains, physical pleasure and satisfaction of men’s ego. To defy subordination, material ecofeminism encourages empowering women through better education and financial self-sustenance. Ecofeminism also engenders the idea of liberation of women for ecological protection. Owing to their intimate relationship, innate affection, and endowed spiritual linkage with nature, women can play a vital role in the protection of the environment, if given a chance. This research endeavours to establish that females are living beings. They have feelings. They are equally passionate beings with ambitions having their own material and physical needs. The study concludes that akin to other living beings, their potential is also defined by their determination and audaciousness. They have the ability to transcend all the impediments created by patriarchal subjugation.